EDUKASI KEPATUHAN PASIEN TB MELALUI APLIKASI TOBAT (TEKUN MINUM OBAT) - Fahrunnisa, Fahrunnisa (STIKES Advaita Medika Tabanan, 2023)
Medical-surgical nursing residency practice is part of the educational process that focuses on developing clinical skills, especially in the respiratory system. Tuberculosis is a disease caused by mycobacterium tuberculosis bacteria that is transmitted through the air where coughing and sneezing are sources of transmission that release tuberculosis bacilli that float in the air in aerosols or small granules (Saktiawati and Sumardi, 2021). In 2021, TB is the second deadliest infectious disease in the world after Covid-19 and is ranked thirteenth as the leading cause of death worldwide (WHO, 2022). The role of nurses that must be carried out is as nursing care providers, researchers, advocates, educators, and innovators. The role carried out as a nursing care provider is to manage 30 patients with TB (Tuberculosis) respiratory system disorders using the Virginia Henderson Theory approach. The nursing problem that often arises is the ineffectiveness of airway clearance in addition to having a role as an innovator and educator, namely motivating to improve compliance with taking medication and providing education using the TOBAT application (diligently taking medicine). Measurement of adherence to taking medication is carried out using the MMS-8 questionnaire (Modified Morisky Adherence Scale-8 via google form with the results before using the TOBAT application (diligently taking medication), there are no high adherence scores, 7 moderate adherence and 23 low adherence, then given education related to the TOBAT application (diligently taking medication) and a post test is obtained with a high adherence score of 24 people and moderate adherence of 6 people so it can be concluded that patients have increased adherence to taking medication with the TOBAT application (diligently taking medication) and it is hoped that all TB patients will adhere to taking medication.